POTENSI EKSTRAK DAUN DAN BUAH Excoecaria agallocha L. TERHADAP HAMA Crocidolomia pavonana F. PADA TANAMAN SAWI PUTIH - Melo, Aneke H.; Maramis, R. T.D.; Warouw, J. (Universitas Sam Ratulangi, 2015)
ABSTRACT Â The purpose of this study is to determine the potential of the extracts of leaves and fruit E. agallocha, to the larvae of C. pavonana mortality and to determine the right concentration / dosage extracts of leaves and fruits E. agallocha in controlling of pests C. pavonana. This research was carried out by several phases: 1) exploration of the source plant material extract; 2) Preparation of feed crops; 3) Taking a test insect; 4) Extraction of plant material source extract; and 5) Extracts application. This research was conducted at Plantation Rurukan Village sub district of East Tomohon, Tomohon city for taking the testing insects and feed maintenance ; Laboratory of Microbiology and Plant Pathology, Department of Plant Pests and Diseases, for the extraction of plant material and extracts application in Tomohon and exploration of extracts of plant material sources in the Rerer village sub district of Kombi,Â District of Minahasa. The results of the Research are leaves and fruit extract E. agallocha can cause mortality of larvae of C. pavonana. With symptoms of larval mortality after treatment of leaves and fruit extracts of E. agalloca lanta is the larvae colored in yellowish pale then turned into brown to black. E. agalloca leaves and fruit has potential as an ingredient vegetable insecticides to control larvae of C. pavonana with concentration at the level of 0.04% is good at treatment leaf extract and fruit extract treatment as well. Key words: extract E. agallocha, pests C. pavonana, white mustard plants